The other Dr. Gilmer : two men, a murder, and an unlikely fight for justice - Gilmer, Benjamin (Ballantine Books, 2022)
"A rural physician learns that a former doctor at his clinic committed a shocking crime, leading him to uncover an undiagnosed mental health crisis in our broken prison system--a powerful true story expanding on one of the most popular This American Life episodes of all time. When family physician Dr. Benjamin Gilmer began working at the Cane Creek clinic in rural North Carolina, he was following in the footsteps of a man with the same last name. His predecessor, Dr. Vince Gilmer, was beloved by his patients and community--right up until the shocking moment when he strangled his ailing father and then returned to the clinic for a regular day of work after the murder. He'd been in prison for nearly a decade by the time Benjamin arrived, but Vince's patients would still tell Benjamin they couldn't believe the other Dr. Gilmer was capable of such violence. The more Benjamin looked into Vince's case, the more he knew that something was wrong. Vince knew, too. He complained from the time he was arrested of his 'SSRI brain,' referring to withdrawal from his anti-depressant medication. When Benjamin visited Vince in prison, he met a man who was obviously fighting his own mind, constantly twitching and veering off into nonsensical tangents. Enlisting This American Life journalist Sarah Koenig, Benjamin resolved to get Vince the help he needed. But time and again, the pair would come up against a prison system that cared little about the mental health of its inmates--despite an estimated one third of them suffering from an untreated mental illness. In The Other Dr. Gilmer, Dr. Benjamin Gilmer tells of how a caring man was overcome by a perfect storm of rare health conditions, leading to an unimaginable crime. Rather than get treatment, Vince Gilmer was sentenced to life in prison--a life made all the worse by his untrustworthy brain and prison and government officials who dismissed his situation. A large percentage of imprisoned Americans are suffering from mental illness when they commit their crimes and continue to suffer, untreated, in prison. In a country with the highest incarceration rates in the world, Dr. Benjamin Gilmer argues that some crimes need to be healed rather than punished"--